1-Ax-B=0

Simple and best practice solution for 1-Ax-B=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-Ax-B=0 equation:


Simplifying
1 + -1Ax + -1B = 0
Reorder the terms:
1 + -1B + -1xA = 0
Solving
1 + -1B + -1xA = 0
Solving for variable 'B'.
Move all terms containing B to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1B + -1 + -1xA = 0 + -1
Reorder the terms:
1 + -1 + -1B + -1xA = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -1B + -1xA = 0 + -1
-1B + -1xA = 0 + -1
Combine like terms: 0 + -1 = -1
-1B + -1xA = -1
Add 'xA' to each side of the equation.
-1B + -1xA + xA = -1 + xA
Combine like terms: -1xA + xA = 0
-1B + 0 = -1 + xA
-1B = -1 + xA
Divide each side by '-1'.
B = 1 + -1xA
Simplifying
B = 1 + -1xA

You can always share this solution

See similar equations:

| 13-(-5)=x | | 2+x/3=3x/4-1 | | X+a=3/4 | | 7/10+k=9/10 | | 7x+14=3x-70 | | y=-3-(-6) | | h=-t^2+12t+6 | | m-35=-39 | | 167=6-7(1+3k) | | 8+12-w3/2=8 | | 8x+2y=160 | | 5x^2+25-30=y | | 4(2x+3)=3(1+-4x)+-31 | | 31+8b=2(B-5)+5 | | 12z-(-21)=-21+12z | | t+14?=18 | | (-5)+u=-15 | | y=-4/1+1 | | 60m^2+240m+24=0 | | y=-4/1-1 | | (7p-13)/4=9 | | (4x-1)/3x=8 | | 6x-14=2x+14 | | 2-g=8 | | 5/n+2=10/16 | | 5x+3y-56=-3x+18y-194 | | 4(2x+4)=3(1-4x)-31 | | (m^2-7m-6)(7m^2-3m-7)=0 | | 3+7x+50=12x-2 | | -x/4=27 | | 0=2v-4+2 | | lnx=3.4 | | 37-11x=81-x^2 | | -11z-(-4.86)=6.07 | | 16y^2-16y+4= | | 5x+20*30-20x=6*30 | | 5x^2+25-30=0 | | 5p+12-8+2=6(p+4)-2 | | 12-(x+6)=8x-3 | | 6x+6+17x+4=102 | | q=3x+9xz | | 8x-10+58=18+11x | | 9x/14+3/7=9/14 | | -6=3p-3 | | 5-5w^2/w^2+3w-4 | | -6=9+a+4 | | 6y-10=1y+25 | | 10p+89=-10p-51 | | 10p+89=-10p-55 | | 50-3y=75 | | -1/2(18x-22)+1/3(9x-12) | | -3(-3-4v)-9v= | | 12x^2+28x-125=0 | | 5/12+p=6 | | -4(3(x-y-z)-3(2x+y-5z))=p | | 4+3b=24 | | 4a+3=2n+15 | | .66(2(x+y)+4(x+4y))=p | | -(-(-(-9)))=o | | M/y=9/3 | | -5=6k-5+6k | | -6(8(y-7)+9y)-7(5(7(4z+3))-14)=d | | -56+7y= | | 2x(6x-10)=50+x(12x+5) | | 1=1+3a+2a |


Related pages


lcm calculator with solutionaplus cmcssgreatest common factors calculatorhj4prime factorization for 642nwprime factorization of 344x 2-9100-55x780014.72 is what percent of 199.60graph y 3x 4what is 3.6 repeating as a fraction6yisolve log 3x 2 3square root of 28093x2 8x 548.1 is what percent of 240.52.7 as a decimalfinding the lowest common denominator calculator396.17square root of 3.24solve tan2x 1prime factorization of 310hcf of 75factor 3x 2 2x 2secx cosx sinx2y 3x 0factor tree for 125simplify 4b x 2cq mcdeltaty 2 3x 1 graph4y 6x 2divide improper fractions calculator168-2596-300simplify square root of 3005x 2y 2100-78bodmas equationsroman numerals to 5000factorization calculatorhow do you graph 2xprime factorization of 300what is 5 of 21what is the greatest common factor of 120csxc 1lcm of 6 7 96x 3yequation simplifier with stepsmx3x0.625 as fractionfinding derivatives of lnprime factorization for 2162x-3 factoredlogarithmic derivative calculator2x 6y 103z2step by step derivative calculatorderivative of cosx sinxequation solver with absolute value1921 in roman numerals799.9prime factorization of 180tan 4x-sec 4xcosx cos-xlcm of 150110-22largest common denominator calculatorsolve p 2l 2w for wdifferentiation of sin 2x